A phase II study of cyclophosphamide, etoposide, vincristine and prednisone (CEOP) Alternating with Pralatrexate (P) as front line therapy for patients with peripheral T‐cell lymphoma (PTCL): final results from the T‐ cell consortium trial. (2nd December 2015) - Advani, Ranjana H.; Ansell, Stephen M.; Lechowicz, Mary J.; Beaven, Anne W.; Loberiza, Fausto; Carson, Kenneth R.; Evens, Andrew M.; Foss, Francine; Horwitz, Steven; Pro, Barbara; Pinter‐Brown, Lauren C.; Smith, Sonali M.; et al.
Summary: Peripheral T‐cell lymphomas (PTCL) have suboptimal outcomes using conventional CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy. The anti‐folate pralatrexate, the first drug approved for patients with relapsed/refractory PTCL, provided a rationale to incorporate it into the front‐line setting. This phase 2 study evaluated a novel front‐line combination whereby cyclophosphamide, etoposide, vincristine and prednisone (CEOP) alternated with pralatrexate (CEOP‐P) in PTCL. Patients achieving a complete or partial remission (CR/PR) were eligible for consolidative stem cell transplantation (SCT) after 4 cycles. Thirty‐three stage II‐IV PTCL patients were treated: 21 PTCL‐not otherwise specified (64%), 8 angioimmunoblastic T cell lymphoma (24%) and 4 anaplastic large cell lymphoma (12%). The majority (61%) had stage IV disease and 46% were International Prognostic Index high/intermediate or high risk. Grade 3–4 toxicities included anaemia (27%), thrombocytopenia (12%), febrile neutropenia (18%), mucositis (18%), sepsis (15%), increased creatinine (12%) and liver transaminases (12%). Seventeen patients (52%) achieved a CR. The 2‐year progression‐free survival and overall survial, were 39% (95% confidence interval 21–57) and 60% (95% confidence interval 39–76), respectively. Fifteen patients (45%) (12 CR) received SCT and all remained in CR at a median follow‐up of 21·5 months. CEOP‐P did not improve outcomes compared to historical data using CHOP. Defining optimal front line therapy in PTCL continues to be a challenge and an unmet need.